Anthropometrically-Based Surgical Technique for Tessier 3 Cleft Reconstruction. Issue 8 (November 2016) - Morgan, Aaron L.; Cason, Roger; El Amm, Christian A.
Abstract : Abstract: Craniofacial clefts are rare entities, with an incidence reported as 1.43 to 4.85 per 100, 000 births. The Tessier number 3 cleft, the most medial of the oblique clefts, can manifest as clefting of the lip between the canine and lateral incisors, colobomas of the nasal ala and lower eyelid, and inferior displacement of the medial canthus—frequently disrupting the lacrimal system with extreme variability in expressivity (Eppley). Literature on cleft lip repair is extensive and has evolved to incorporate anthropometric techniques, based on identifiable landmarks and anthropometric measurements that are compared with contralateral unaffected anatomy or population means and tracked over time to assess impact on growth. Recent focus has been placed on "subunit" repair that repairs "like with like." These approaches have resulted in a remarkable reproducibility of methods and outcomes. Facial cleft surgery publications are sparse due to the rarity of the disorders, and consensus has yet to develop on standardized landmarks, reference measurements, and principles of repair. The authors describe a method of correcting incomplete unilateral Tessier 3 cleft based on the principles described above. Intraoperative photographs, including secondary revisions, as well as immediate and long-term postoperative results are presented.